PENGARUH PEMBERIAN MODELLING AUDIO VISUAL TERHADAP PERKEMBANGAN KOGNITIF DI TK TUNAS HARAPAN KARANGASEM JENU TUBAN - Novia Dwi Astuti, Novia Dwi Astuti; Himmatun Nadlifahn, Himmatun Nadlifahn (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
Problems of children who are difficult to concentrate and understand each learning material delivered leads to low attention and activities of children in learning, the child's attention in learning is part of the child's cognitive development. The cognitive development of preschoolers can develop well if supported by effective learning media. The purpose of this study to determine the effect of audio visual modeling on cognitive development in learning in preschool age children in Tunas Harapan kindergarten Karangasem Jenu Tuban.The design of this study is Pre Experiment with One-group Pre-Post Test Design approach. Population used in this study is children in Tunas Harapan kindergarten Karangasem Jenu Tuban . Samples were taken used simple random sampling which amounted to 33 respondents. Data collection is done using observation sheet. Independent variable in this research is the giving audio visual modeling, while the dependent variable is cognitive development in learning, the instrument used in the form of Observation and SOP. Analysis of this study used Wilcoxon test.Wilcoxon test results obtained significant results ? = 0.05 obtained value ? = 0,000 where 0.000 ? 0.05, then H0 rejected, meaning it can be concluded that there is an effect of audio visual modeling of cognitive development in learning in preschoolers.The results of this study recommends for Tunas Harapan kindergarten institutions for audio-visual modeling can be applied in further teaching and learning activities to improve cognitive development.